2002
DOI: 10.1002/mpo.1288
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of minor anomalies in children with hematologic malignancies

Abstract: Eine molekulare russische Puppe stellt die Einschlussverbindung [(M+⊂Krone)⊂Ga4L6]11− (M+=Li+, Na+, K+; Krone=[12]Krone‐4, [15]Krone‐5, [18]Krone‐6) dar. Sie entsteht durch Komplexierung des Metallkations durch den Kronenether und den Einschluss des gebildeten Kation‐Kronenether‐Komplexes in den tetraedrischen [Ga4L6]12−‐Cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…Our results, together with those of Méhes et al 18 and Durmaz et al, 21 allow us to identify it as a morphological characteristic associated with children with leukaemia. The reported association with CALS, 19,20,27,28 also observed by us, has been confirmed in the absence of neurofibromatosis or other entities associated with CALS. 7,8 The association between CALS and leukaemia is interesting, as it also illustrates the phenotypic overlap that exists between patients with multifactorial cancer and monogenic cancer syndromes, a fact that may contribute to the future identification of causal genes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results, together with those of Méhes et al 18 and Durmaz et al, 21 allow us to identify it as a morphological characteristic associated with children with leukaemia. The reported association with CALS, 19,20,27,28 also observed by us, has been confirmed in the absence of neurofibromatosis or other entities associated with CALS. 7,8 The association between CALS and leukaemia is interesting, as it also illustrates the phenotypic overlap that exists between patients with multifactorial cancer and monogenic cancer syndromes, a fact that may contribute to the future identification of causal genes.…”
Section: Discussionsupporting
confidence: 80%
“…Despite these limitations, the previous studies 18---21,27 and our own agree in finding that children with leukaemia have an excess of MPVs, which indicates that one or more prenatal factors cause both MPVs and cancer, although they have not enabled us to identify the associated types of MPVs conclusively. The MPVs that seem to emerge by showing an association or statistically significant differences in children with leukaemia in at least 2 or more studies include variations in palmar flexion creases, 18,21 pigmented naevi 19,20 and café-au-lait spots (CALS), 19,20,27 whilst hypertelorism, epicanthus, synophrys, high arched palate, low-set ears, absent ear lobule, syndactyly, clinodactyly and hallux valgus are MPVs reported in a single study. 21 A Sydney crease is a variation in the palmar flexion creases originally described in children with leukaemia by Menser and Purvis-Smith, and is an age-dependent feature, 39 defined as an extension of the five-finger crease to the ulnar border of the palm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies also have suggested that children with minor malformations or variants, including "birthmarks," may have an increased risk, [7][8][9][10][11] and these could be a marker of "altered prenatal development." 12 A significant increased frequency of birthmarks in children with acute lymphoblastic leukemia (ALL) and rhabdomyosarcoma has been reported in 3 studies.…”
mentioning
confidence: 99%
“…Estimating the real prevalence of this minor anomaly is quite difficult [8]. syndromes and malignant neoplasms [9].…”
mentioning
confidence: 99%